Peranan Komunikasi Efektif dalam Keberhasilan Pendidikan - Rahimudin (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2016)
Communication is one part of the needs of human life. Communication can be interpreted as a relationship (interaction) between one with another. The need for communication will continue as long as humans are still having interactions, both interactions with Allah SWT, with himself, with other humans and interactions with other creatures of Allah SWT. An interesting problem with the role of effective communication in education is because there is still a lot of communication between humans, especially in the field of education which is lacking or ineffective. Therefore, there is a miscommunication among the components that cause education to not work well. The purpose of this paper is the author wants to present the concepts of effective communication so that they can be understood and applied well in educational activities by parents at home, teachers at school and also elements of society. The method and approach used by the author in conducting this writing is content analysis. Library research, data analysis, and phenomenological approach. The conclusion of this study is that communication will be successful if the communication elements consisting of communicators, communicants, communicators, channels, and effects can function properly. The application of effective communication concepts in Islamic education is very important to be done well so that the success and quality of education can be further improved. This paper is expected to contribute to the development of social values ​​and academic values, both in the informal, formal and non-formal education environments by understanding the importance of improving the quality of education through the application of effective communication concepts in these educational environments.